Establishing the success factors for adoption of mobile shopping in Kenya’s retail industry - Ndegwa, Evans Ndungu (Strathmore University, 2013)
Globally, mobile shopping is a multi-billion industry which has been observed to grow at a fast pace. Mobile shopping is one of the electronic commerce types and is at times referred to as mobile storefront. In Kenya, the retail outlets have not been able to deploy mobile shopping for their stores. Despite the high mobile penetration experienced across the country and the relatively high literacy levels, we are yet to see the first mobile shopping deployment. What could be the problem? Why is this multi-billion industry not breaking ground in Kenya? This research paper intends to find out what are the success factors that can lead to adoption of mobile shopping in Kenya viewed from both a retailer and a consumer perspective. The paper also sought to find out if there have been other successful models in other parts of the world and if these models could be replicated here in Kenya. To achieve this, this research made use of different research tools. The research involved development of a mobile shopping model application that was used as a proof of concept in this research. It is against this application together with a questionnaire and a set of interview questions that data was collected and analyzed. From the results obtained, the main factors that could lead to successful adoption are ease of use, usefulness, availability of reliable real-time prices, reusable shopping lists and the ability to compare features and prices of related goods. However, problems in delivery of goods ordered, poor security, fraud and poor application design are some of the factors that can lead to lack of adoption of such an application. It was also found that other successful models have been launched by retail giants such as Wal-Mart, Kruger and Costco, which with few modifications to suit the Kenyan scenario, can be replicated. This paper recommends further research in the factors that make customers prefer one retail outlet to the other to shed more light into other dynamics that may influence introduction of mobile shopping strategy.
Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Telecommunication, Innovation and Development (MSc TID) at Strathmore University
Keywords: Mobile shopping; Kenya